2012
DOI: 10.1093/molbev/mss241
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Dynamics of Small RNA Response to a Retroelement Invasion in Drosophila

Abstract: Although small RNAs efficiently control transposition activity of most transposons in the host genome, such an immune system is not always applicable against a new transposon's invasions. Here, we explored a possibility to introduce potentially mobile copy of the Penelope retroelement previously implicated in hybrid dysgenesis syndrome in Drosophila virilis into the genomes of two distant Drosophila species. The consequences of such introduction were monitored at different phases after experimental colonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…Few TEs show aberrant expression in the hybrid sterile males compared with C. nigoni males Overexpression of TEs is frequently found in F1 hybrids and is associated with male sterility (Rozhkov et al 2013;Erwin et al 2015). We wondered whether misregulation of TEs might be associated with the observed male sterility in the introgression lines despite the fact that they were subjected to backcrossing for at least 15 generations (Bi et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Few TEs show aberrant expression in the hybrid sterile males compared with C. nigoni males Overexpression of TEs is frequently found in F1 hybrids and is associated with male sterility (Rozhkov et al 2013;Erwin et al 2015). We wondered whether misregulation of TEs might be associated with the observed male sterility in the introgression lines despite the fact that they were subjected to backcrossing for at least 15 generations (Bi et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This supposition is supported by studies of P elements and Penelope, a Drosophila virilis transposon artificially introduced into Drosophila melanogaster. Acquisition of the ability to control these elements was associated with their integration into piRNA clusters (Ronsseray et al 1998;Brennecke et al 2008;Khurana et al 2011;Rozhkov et al 2013).…”
mentioning
confidence: 99%
“…Different mutants in the piRNA pathway can be associated with different types of derepressed TEs [Vagin et al, 2006;Chen et al, 2007;Chambeyron et al, 2008]. Malfunction of epigenetic controls results in transcriptional activation and mobilization of TEs in Drosophila dysgenic hybrids and can also involve changes in chromatin structure and modification [Blumenstiel and Hartl, 2005;Girard and Hannon, 2008;Rozhkov et al, 2010Rozhkov et al, , 2013.…”
Section: Hybrid Dysgenesis and Mechanisms Of Retrotransposon Silencinmentioning
confidence: 99%
“…Initially, maternally deposited siRNAs homologous to Penelope were reported in P-like strains but were absent from M-like strains [Blumenstiel and Hartl, 2005]. A more thorough analysis of small RNAs in D. virilis was performed by Rozhkov et al [2010Rozhkov et al [ , 2013, where Penelope was shown to be targeted by antisense siRNAs, and only a small proportion represented the 23-29-nt piRNA fraction, which could be related to germline silencing. The introduction of active Penelope into D. melanogaster , which has no preexisting Penelope copies in the genome, caused induction of both sense and antisense siRNAs in the transformed strains, suggesting that the siRNA pathway could play an important role at the initial stages of TE invasion, acting similar to an antiviral response.…”
Section: Hybrid Dysgenesis and Mechanisms Of Retrotransposon Silencinmentioning
confidence: 99%
See 1 more Smart Citation